Economic Valuation of Stevia Sweetener: Double-Bounded Dichotomous Choice Study in East Java - Nurul Lailatus Sholehah; Silvana Maulidah; Riyanti Isaskar (Jurnal Manajemen dan Agribisnis, 2026)
Background: Sugar consumption in Indonesia reaches 160 grams per day, six times the WHO recommendation, contributing to 20.4 million diabetes cases (ranked 2nd globally). Stevia rebaudiana Bertoni offers a promising natural, zero-calorie sweetener alternative; however, its market adoption in Indonesia remains hindered by high prices, consumer perceptions, and a lack of empirical economic valuation data.Purpose: This study aimed to analyze consumer willingness to pay (WTP) for stevia-based sweetener products in East Java and examine the factors influencing this decision.Design/methodology/approach: The study employed the Contingent Valuation Method with Double-Bounded Dichotomous Choice format on 200 respondents in East Java. Factor analysis utilized ordered logit regression with independent variables that included sociodemographic characteristics, diabetes status, knowledge of stevia, perceptions of price and quality, and health consciousness.Findings/Result: Consumers in East Java demonstrated a strong premium WTP for stevia sweeteners, exceeding current market prices by more than 50%. Product knowledge and health consciousness emerged as the most influential determinants, indicating that health-related motivations substantially shape consumer valuation. Conclusion: East Java consumers demonstrated substantial premium WTP for stevia sweeteners, with product knowledge and health consciousness as primary determinants, indicating the importance of health education strategies and product value communication to increase stevia sweetener product adoption in Indonesia.Originality/value (State of the art): This study contributes to the limited literature on the economic valuation of healthy sweetener products in developing countries with high sugar consumption, using the CVM-DBDC approach to identify specific determinants of consumer decisions in adopting natural sweeteners as substitutes for conventional sugar. Keywords: contingent valuation method, double-bounded dichotomous choice, health consciousness, stevia sweetener, willingness to pay